Progress of polymer-based strategies in fungal disease management: Designed for different roles - Wu, Siyu; Guo, Wenlai; Li, Bo; Zhou, Huidong; Meng, Hongqi; Sun, Junyi; Li, Ruiyan; Guo, Deming; Zhang, Xi; Li, Rui; Qu, Wenrui (Frontiers in Cellular and Infection Microbiology, 2023)
Fungal diseases have posed a great challenge to global health, but have fewer solutions compared to bacterial and viral infections. Development and application of new treatment modalities for fungi are limited by their inherent essential properties as eukaryotes. The microorganism identification and drug sensitivity analyze are limited by their proliferation rates. Moreover, there are currently no vaccines for prevention. Polymer science and related interdisciplinary technologies have revolutionized the field of fungal disease management. To date, numerous advanced polymer-based systems have been developed for management of fungal diseases, including prevention, diagnosis, treatment and monitoring. In this review, we provide an overview of current needs and advances in polymer-based strategies against fungal diseases. We high light various treatment modalities. Delivery systems of antifungal drugs, systems based on polymers’ innate antifungal activities, and photodynamic therapies each follow their own mechanisms and unique design clues. We also discuss various prevention strategies including immunization and antifungal medical devices, and further describe point-of-care testing platforms as futuristic diagnostic and monitoring tools. The broad application of polymer-based strategies for both public and personal health management is prospected and integrated systems have become a promising direction. However, there is a gap between experimental studies and clinical translation. In future, well-designed in vivo trials should be conducted to reveal the underlying mechanisms and explore the efficacy as well as biosafety of polymer-based products.